Implementation Of People Centered Development Model in Village Development (Theoretical Study Of Agil Talcot Parsons) - Irfan, Agus (International Journal of Advanced Multidisciplinary, 2023)
Village development, which is entirely taken from the local community, is now seen as a key component of village development. Each village is given autonomy to carry out development in accordance with its potential. Objectives this research how the village sees the potential can contribute support to its development, where this potential lies in empowered humans/communities, thus making human-centered development. The theory of this research is people centered development, AGIL Talcot Parsons. This research method is descriptive qualitative with a theoretical study analysis method approach. The implementation of village development through human-centered development, in adaptation is the concept of community survival with various types of changes, in terms of achieving the goal is to carry out mutual cooperation, kinship, and solidarity for the purpose of achieving peace and social justice, in integration. The conclusion of this study is that the four functions of AGIL are interrelated with one another.